Association between Clinical/Radiographic Characteristics and Histopathological Diagnoses of Periapical Granuloma and Cyst - Banomyong, Danuchit; Arayasantiparb, Raweewan; Sirakulwat, Kanoknuch; Kasemsuwan, Jane; Chirarom, Nannaphat; Laopan, Nithiporn; Lapthanasupkul, Puangwan (European Journal of Dentistry, 2023)
Objective The aim of this study was to determine the association between clinical/radiographic characteristics and histopathological diagnoses of periapical granuloma and cyst obtained from the teeth treated with endodontic microsurgery.Materials and Methods The clinical, radiographic (periapical and cone-beam computed tomography), and histopathological data were collected from patients' dental records of endodontic microsurgery on the teeth with periapical lesions. These lesions were histopathologically diagnosed as either granuloma or cyst, at the Endodontic Clinic, Faculty of Dentistry, Mahidol University, Bangkok, Thailand, from 2016 to 2021 according to inclusion and exclusion criteria. The data were analyzed using bivariate analysis and a multinomial logistic regression at a significance level of p-value less than 0.05.Results A total of 83 patients (58 females and 25 males) with an average age of 45 to 49.5 years old met the criteria including 68 periapical granulomas (81.9%) and 15 periapical cysts (18.1%). A periapical lesion involving multiple teeth in a periapical radiograph was significantly associated with the histopathological diagnosis of periapical cyst (p < 0.05). Such periapical lesion was six times more likely to be periapical cyst than periapical granuloma.Conclusions A significant factor for predicting periapical cyst from periapical granuloma was the presence of a periapical lesion with multiple-teeth involvement in a dental radiograph.
Keywords: dental radiograph; endodontic microsurgery; granuloma; histopathology; periapical cyst